Sex, Sickness, and Slavery : Illness in the Antebellum South - Weiner, Marli Frances, 1953- (Book collections on Project MUSE., 2012)
This study of medical treatment in the antebellum South argues that Southern physicians' scientific training and practice uniquely entitled them to formulate medical justification for the imbalanced racial hierarchies of the period.